PERGESERAN PERILAKU KONSUMEN DALAM MINAT BELI ULANG BERDASAR PRODUK WEBSITE (ANALISIS PERUBAHAN MODEL BISNIS TERHADAP PILIHAN KONSUMEN) - Arizal Hamizar (IAIN Ambon, 2020)
This paper discusses the change in business models that shift to the 4.0-based model in which newspapers which are the object of research change their product platforms from paper to websites at PT. Ambon Press Intermedia. The variables studied are the product and its effect on consumer behavior in using the value obtained which is reflected in the variable repurchase interest. The results showed that there was a significant relationship between information richness (richness of content), reliability of information (reliability of Content) and the appearance of the website (interface of website) on the behavior (Behavior) to consume sustainably. Keywords: e-products, repurchase interests, consumer behavior